2023
DOI: 10.3389/fphar.2023.1150270
|View full text |Cite|
|
Sign up to set email alerts
|

Stylopine: A potential natural metabolite to block vascular endothelial growth factor receptor 2 (VEGFR2) in osteosarcoma therapy

Abstract: Vascular endothelial growth factor (VEGF) signals cell survival, cell migration, osteogenesis, cell proliferation, angiogenesis, and vascular permeability by binding to VEGF receptor 2 (VEGFR-2). Osteosarcoma is the most common primary bone cancer, majorly affects young adults. Activation of VEGFR-2 signaling is a therapeutic target for osteosarcoma. The present study aimed to evaluate the potency of stylopine in regulation of the VEGFR-2 signaling pathway and its anti-tumour effect human MG-63 osteosarcoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…There is strong evidence indicating that tumour metastasis and prognosis are directly related to the degree of VEGF expression (Jianzhang et al, 2023). In osteosarcoma, VEGF signalling suppression induces apoptosis and halts cell development (Velayutham et al, 2023). Singh et al, (2023) have investigated the anti-cancer effects in both invitro and invivo studies by encapsulated into nanoparticles and found that the MgO-NH-PBA-Rutin nanohybrid signi cantly reduced the growth and migration of MDA-MB-231 cells by inducing apoptosis and intracellular production of reactive oxygen species in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence indicating that tumour metastasis and prognosis are directly related to the degree of VEGF expression (Jianzhang et al, 2023). In osteosarcoma, VEGF signalling suppression induces apoptosis and halts cell development (Velayutham et al, 2023). Singh et al, (2023) have investigated the anti-cancer effects in both invitro and invivo studies by encapsulated into nanoparticles and found that the MgO-NH-PBA-Rutin nanohybrid signi cantly reduced the growth and migration of MDA-MB-231 cells by inducing apoptosis and intracellular production of reactive oxygen species in breast cancer.…”
Section: Introductionmentioning
confidence: 99%